Changes in taste sensation of sour, salty, sweet, bitter, umami, and spicy, as well as levels of malondialdehyde serum in radiographers - Agniz Nur Aulia; Jenny Sunariani; Ester Arijani Rachmat (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2016)
Background: Radiation used for any purpose certainly contains potential danger to humans. Radiographers are given a task, authority, and responsibility by the competent authority to conduct radiography and imaging in health services unit. Some researcheson the effects of radiation on cancer patients show that radiation can cause an increase in bitterness and metal taste [in cancer patients] leading to discomfort in the oral cavity. In body, free radicals then can cause lipid peroxidation process. Lipid peroxidation is an oxidative destruction of polyunsaturated fatty acid producing malondialdehyde (MDA). Purpose: This study aimed to determine the effects of radiation on changes in the taste sensation of sour, salty, sweet, bitter, umami, and spicy as well as the levels of MDA serum in radiographers. Method: This study was an observational laboratory research using post- test control design. Samples were selected using simple random sampling technique. The samples were seven radiographers who have been working for five years in the laboratory and radiographic units in Surabaya. Result: Based on the results of statistical tests, it showed that there were no differences in the sensitivity of all tastes between the groups tested. Moreover, the results also depicted considerable value for the sour taste was 0.550, the saltiness was 0.775, the sweetness was 0.294, the bitter taste was 0.065, the umami taste was 0.705, and the spicy taste was 0.319 (p>0.05). However, the dramatic increase was higlighted in levels of MDA serum with a significant value of 0.065 (p>0.005). Conclusion. There were no changes in the sensitivity of sour, salty, sweet, bitter, umami, and spicy tastes, but there was a significant increased in level of MDA serum in the radiographers compared to the control group.